GE_GERICHTE C/5448/2018 vom 27. August 2018 - GE Cour de justice (2018)
HYPOTHÈQUE LÉGALE DES ARTISANS ET ENTREPRENEURS ; RÉQUISITION D'INSCRIPTION ; PROVISOIRE | CC.837.al1.ch3; CC.961.al3; CC.839.al2